2021
DOI: 10.1080/17430437.2021.1903438
|View full text |Cite
|
Sign up to set email alerts
|

The urban and economic impacts of mega-events: mechanisms of change in global games

Abstract: Mega-events are global affairs with profound effects across a variety of scales, and are the focus of a large and growing body of academic inquiry. This special section in Sports in Society centers on the urban and economic impacts of mega-events on the societies that host them, offering an examination of individual cases and emerging patterns. The authors explore different dimensions of the recent mega-event experience from around the world, proposing novel ways of theorizing these outsized expressions of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The study of Breus (2007) also showed the positive impact of the 2006 World Cup on economic growth in Germany and Munich in particular. We also find the study of Wolfe et al (2021) and Do et al (2021) study, which also show the positive impact of hosting mega sporting events such as the Olympics games and the FIFA World Cup on urban development in the host cities.…”
Section: -Conclusionsupporting
confidence: 61%
See 1 more Smart Citation
“…The study of Breus (2007) also showed the positive impact of the 2006 World Cup on economic growth in Germany and Munich in particular. We also find the study of Wolfe et al (2021) and Do et al (2021) study, which also show the positive impact of hosting mega sporting events such as the Olympics games and the FIFA World Cup on urban development in the host cities.…”
Section: -Conclusionsupporting
confidence: 61%
“…The study of Wolfe et al (2021) [13] illustrates the role and importance of mega-events, particularly the Olympic Games, the FIFA World Cup, and the Commonwealth Games, in spreading urban space and their positive impact on the urban development of the cities hosting these sporting events, as well as their impact on politics, trade, and culture. What distinguishes this study is that it provides modern and innovative ways to understand the effect of mega-events on individuals, communities, and host cities.…”
Section: -Literature Reviewmentioning
confidence: 99%
“…Future studies should include researching sporting event visitors' characteristics as this is a starting point for decisions regarding promotion of the event as well as preparation of the city (destination) since events are an integral part of a city's offer and are inevitably linked to it [60], whether they are mega or major.…”
Section: Discussionmentioning
confidence: 99%
“…Since events are inextricably linked to the cities that host them [60], of interest for this paper are spectators and their satisfaction and intentions to return to the destination where the event was held. Customer satisfaction in the case of sporting event spectators has been defined as a "pleasurable, fulfilment response to the entertainment of a sport competition and/or ancillary services provided during a game" [35] (p. 340).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, we will not know the impact of hosting a closed mega-event like the Tokyo 2020 Olympics for several years. Finally, the perceived economic value is often the main reason for hosting sport mega-events (Wolfe et al, 2021 ). It was projected that hosting the Tokyo Olympics without spectators would result in a financial loss of up to 2.4 trillion yen in Japan (Blair, 2021 ).…”
Section: Introductionmentioning
confidence: 99%